Is there a massive glacial-Holocene flora continuity in Central Europe? - Molnár, Ábel Péter; Demeter, László; Biró, Marianna; Chytrý, Milan; Bartha, Sándor; Gantuya, Batdelger; Molnár, Zsolt (Biological reviews of the Cambridge Philosophical Society, 2023)
The prevailing paradigm about the Quaternary ecological and evolutionary history of Central European ecosystems is that they were repeatedly impoverished by regional extinctions of most species during the glacial periods, followed by massive recolonizations from southern and eastern refugia during interglacial periods. Recent literature partially contradicts this view and provides evidence to re-evaluate this Postglacial Recolonization Hypothesis and develop an alternative one. We examined the long-term history of the flora of the Carpathian (Pannonian) Basin by synthesising recent advances in ecological, phylogeographical, palaeoecological and palaeoclimatological research, and analysing the cold tolerance of the native flora of a test area (Hungary, the central part of the Carpathian Basin). We found that (1) many species have likely occurred there continuously since before the Last Glacial Maximum (LGM); (2) most of the present-day native flora (1404 species, about 80%) can occur in climates as cold as or colder than the LGM (mean annual temperature ≤+3.5°C); and (3) grasslands and forests can be species-rich under an LGM-like cold climate. These arguments support an alternative hypothesis, which we call the Flora Continuity Hypothesis. It states that long-term continuity of much of the flora in the Carpathian Basin is more plausible than regional extinctions during the LGM followed by massive postglacial recolonizations. The long-term continuity of the region's flora may have fundamental implications not only for understanding local biogeography and ecology (e.g. the temporal scale of processes), but also for conservation strategies focusing on protecting ancient species-rich ecosystems and local gene pools.
Keywords: fylogeografie; Last Glacial Maximum; Phylogeography; ekosystém; recolonization; Europe; refugia; Pleistocene; Evropa; biodiversity conservation; genetická variace; vegetation history; Genetic Variation; Carpathian Basin; fylogeneze; phylogeography; Ecosystem; Phylogeny; paleoecology